Vile e gentile: La nobiltà in Dante tra generazione e predestinazione - Lenzi, Massimiliano (Studi e materiali di storia delle religioni, 2020)
This study is dedicated to the thematization of the base/gentle contrast, which is crucial to Dante's definition of nobility. By highlighting the remarkable theoretical and poetic coherence of these concepts, the paper reconstructs their implications - both theological and philosophical (primarily related to the natural phenomenon of generation) - and infers that those who are predestined are equated with the noble and "well-born". Nobility, then, is a fact of nature - but a nature interpreted as a divine creation, i.e. as an instrument of the creator's will that always predisposes the good birth of those it wants to save.